ORGANIZATIONAL AND LEGAL REGULATION OF COUNTERING ILLEGAL MIGRATION IN THE SYSTEM OF NATIONAL SECURITY OF UKRAINE - Vasiliev V.T. (Pressing Problems of Public Administration, 2018)
The problems of counteraction to illegal migration in Ukraine are investigated and ways of theirsolution in the system of providing national security of Ukraine for formation and implementation ofthe state migration policy in the conditions of decentralization are offered.